IMPROVEMENT OF ROAD TRAFFIC QUALITY IN ACCIDENT CLUSTERS - D. V. Kapsky (Наука и техника)
Road traffic with its share from 2/3 to 3/4 of the total volume of transport service represents rather large and complicated social and production system with several subsystems that include roads, transport facilities, road traffic organization, law enforcement, personnel training, road traffic service and others. Road traffic quality can be quantitatively evaluated in accordance with values of losses pertaining to social and economic cost of discretionary (unenforced) expenses for road traffic process. Road traffic contains accident, ecological, economic and social risks. Accidence is considered as the most important risk for participants involved in road traffic because it directly concerns their life, health and welfare. So accident response has rather high social significance and it is considered as a matter of national importance. In this connection role of road traffic organization has become very important and it is directed on improvement of its quality including security in the accident clusters.Methodological principles for improvement of road traffic quality have been developed in the paper. These principles presuppose the following: maximization of danger while selecting investigation object; minimization of total losses while evaluating quality and selecting solutions on improvement in road traffic safety; balanced accountability of accidental and ecological losses while selecting solutions on higher road traffic safety in ambiguous situations; minimization of total cost pertaining to object operation while selecting measures on improvement of road traffic safety; obligatory operative control evaluation of accidence on the basis of method for conflict situations while introducing measures of road traffic safety. Such approaches will contribute to higher quality of the decisions taken in the field of road traffic organization.